Influence of Participatory Project Initiation on Sustainable Forest Management in Saboti, Trans-Nzoia County, Kenya - Anthony Tabot; Ochieng Owuor; Joash Migosi (International Journal of Forestry Research)
Forestry related projects fail due to the lack of participation by the community during the initiation stage. This further leads to unsustainable management of forests. This study was undertaken to examine how participatory project initiation influences sustainable forest management in Saboti forest in Trans-Nzoia County, Kenya. Participatory Development Theory guided this study. The explanatory research design was adopted. The target population was 2600 community forest association (CFA) members and 15 Kenya Forest Officers. Census sampling was used in the sampling of Kenya forest Officers and simple random sampling to select community forest management members. The sample size was 347 community forest management members and 15 Kenya forest Officers. Data were collected using questionnaires and through interview. Data were analyzed using descriptive and inferential statistics. Presentation of findings was carried out using tables. There was a significant influence of participatory project initiation on sustainable forest management (SFM) (r = 0.700, p=0.00). This implies that an increase in participatory project initiation improved sustainable forest management in Saboti. Participatory project initiation had a significant influence on sustainable forest management. The community participation in initiation had a significant influence on sustainable forest management. There is need for forest management to involve the community members during the initiation stage of the projects in order to achieve sustainable forest management.